2006
DOI: 10.1002/bit.21221
|View full text |Cite
|
Sign up to set email alerts
|

Production of bio‐hydrogen by mesophilic anaerobic fermentation in an acid‐phase sequencing batch reactor

Abstract: The pH and hydraulic retention time (HRT) of an anaerobic sequencing batch reactor (ASBR) were varied to optimize the conversion of carbohydrate-rich synthetic wastewater into bio-hydrogen. A full factorial design using evolutionary operation (EVOP) was used to determine the effect of the factors and to find the optimum condition of each factor required for high hydrogen production rate. Experimental results from 20 runs indicate that a maximum hydrogen production rate of 4,460-5,540 mL/L/day under the volumet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 56 publications
2
12
0
4
Order By: Relevance
“…Incidentally, in another study, H 2 -producing anaerobic sequencing batch reactor (ASBR) had a higher H 2 production rate, compared with that produced using CSTRs. This study suggested that the H 2 -producing ASBR is a promising bio-system for prolonged and stable H 2 production particularly if enriched H2-producing bacterial populations are achieved [22].…”
Section: Physiology Of Hydrogen Productionmentioning
confidence: 99%
“…Incidentally, in another study, H 2 -producing anaerobic sequencing batch reactor (ASBR) had a higher H 2 production rate, compared with that produced using CSTRs. This study suggested that the H 2 -producing ASBR is a promising bio-system for prolonged and stable H 2 production particularly if enriched H2-producing bacterial populations are achieved [22].…”
Section: Physiology Of Hydrogen Productionmentioning
confidence: 99%
“…91 Outros tipos de reatores também têm sido utilizados, tais como o reator anaeróbio de fluxo ascendente e manta de lodo (upflow anaerobic sludge blanket -UASB), o biorreator de leito empacotado, o reator de leito fixo, o biorreator de leito fixo e fluxo ascendente, o reator batelada anaeróbio em série e o reator de leito fluidizado anaeróbio, entre outros. [92][93][94][95][96][97] Em alguns estudos de produção de H 2 , verificou-se que o processo em batelada apresenta maiores rendimentos de H 2 quando comparado ao modo contínuo. Isto pode ser atribuído ao microambiente substancialmente diferente no reator em batelada quando comparado aos reatores contínuos.…”
Section: Modo Operacional Do Reatorunclassified
“…When this occurs, a compromise must be made. In this system, out of the two response variables, P s and R s , the rate is of more interest since continuous biogas systems operate more optimally at low to mid-range hydraulic retention times [20,21] meaning that maximum conversion is hardly ever achieved. For this reason, more effort should be devoted to maximizing the rate of hydrogen production with partial sacrifice to the conversion efficiency.…”
Section: Specific Hydrogen Production Ratementioning
confidence: 99%